The Romanian Language, a European Language – between Modernism and Europeanization - Mariana Viorica BUDA (Analele Universităţii din Oradea. Relaţii Internaţionale şi Studii Europene, 2022)
The language spoken by a community of people is a complex system of linguistic signs formed during the historic coexistence. The emergence of a language is a large process and it can’t be determined exactly the beginning, even if the specialists establish always a starting moment. The Romanian language passed during the history through several stages of evolution and maturity. In the last Century, the Romanian language entered in its Modern Age, characterized by stability. However, there are important changes, influenced by the French and Italian languages at the begging of the XX Century and English language at the end of the XX Century. The aim of our paper is to describe and analyse the different stages of the Romanian language in the last 100 years and how it was influenced by the major events that Romania went through.